Potential of IRNSS/NavIC L5 signals for ionospheric studies. Issue 10 (15th May 2019) - Sharma, A.K.; Gurav, O.B.; Bose, Anindya; Gaikwad, H.P.; Chavan, G.A.; Santra, Atanu; Kamble, S.S.; Vhatkar, R.S.
Abstract: Indian Space Research Organization (ISRO) has developed an indigenous system named Indian Regional Navigation Satellite System (IRNSS) or NavIC (Navigation with Indian Constellation), that consists of 7 satellites and transmits navigation signal in L and S bands. ISRO, for validation of the system, has installed many IGS (IRNSS/GPS/SBAS) receivers scattered over the Indian region. Using preliminary data from two geographically widely separated stations over India, this paper presents the results on studies on parameters of IRNSS signal quality and discusses how these parameters may be used to study the ionospheric behavior over the Indian region. The results show the importance and advantages of using IRNSS data for such studies.